Dynamic Analysis of a Prey Predator Model with Holling-Type III Functional Response and Anti-Predator Behavior - Umaroh, Siti Zulfaniah; Savitri, Dian (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The prey-predator model in this article reviews the interaction of two populations with a type III Holling -type III functional response and anti-predator behavior. The dynamic analysis starts by determining the basic model construction assumptions, equilibrium and stability points, and numerical simulations using Python. Dynamic analysis results obtained four equilibrium points with types of stability, namely. which is unstable, which is asymptotically stable , and . Which is stable under certain conditions. The numerical simulation results show double stability at the equilibrium points. and with the anti-predator behavior parameter value . The anti-predator parameter value indicates a change in stability that is only the equilibrium point. Differences in the values of the anti-predator behavior parameters affect changes in system solutions and impact reducing predator populations.